Influence of Service Quality, Ease of Use of Applications on Loyalty with Customer Satisfaction as a Mediation - Haq, Muhammad Achiril; Handayanto, Eko; Rumijati, Aniek (University of Muhammadiyah Malang, 2022)
This study was conducted to determine the effect of service quality, ease of use of the application on loyalty with customer satisfaction as a mediating variable. Methods Data collection uses a survey. The sampling technique was purposive random sampling with a total of 160 Go-Car and Go-Ride service users.The study used path analysis techniques and to test the mediating variables using the Sobel Test. The results showed that service quality and ease of use of the application had a significant effect on customer satisfaction. Service quality has no significant effect on customer loyalty, ease of use of applications has a significant effect on customer loyalty, while customer satisfaction has a significant effect on customer loyalty and customer satisfaction as a mediating variable is able to affect service quality on customer loyalty while customer satisfaction as a mediating variable is not able to affect ease of use. application usage on customer loyalty.